Microvascular cutaneous coverage in wounds that expose the Achilles tendon: case report - Haquet-Guerrero, Penelope J.; Banegas-Ruiz, Rodrigo; Morales-Yépez, Hector A.; Contreras-Sibaja, Eric; Pichardo-Esquivel, Daniel; Hernández-García, Luis M.; Robledo-Madrid, Paúl; Ibarra-López, Julián O.; Rodriguez-Bautista, Julio O.; Rodriguez-García, Nadia A.; Canseco-Fuentes, Miguel Á.; Torre-Anaya, Erik A. (International Journal of Research in Medical Sciences, 2022)
Achilles tendon rupture, being one of the main tendon ruptures present, surgery being the most favourable option even taking into account complications such as infections and skin necrosis, it is necessary to develop techniques which help to reduce complications and increase benefits. The methods follow-up of 2 cases of patients with skin defects in the region of the Achilles tendon in patients who were treated at the "Luis Guillermo lbarra lbarra" national rehabilitation institute during the period 2020-2021 in the Traumatology service, treated with radial free flap forearm, using the description of the most used flaps in the literature. Results in both cases integrity of the free radial forearm flap in its entirety, functional recovery for walking, ability to put shoes back on, and without the need for reoperation, as well as a high level of satisfaction by patients. Conclusions if we are talking about an Achilles tendon rupture with a significant skin defect, the free radial forearm flap is an adequate option, if we are talking about a complete defect, the composite flap is the best option, remember that the decision on what type of flap will be used will depend on of the size of the lesion.